THE COMMUNICATIVE ACTIVITIES IN â€œBRIGHT AN ENGLISHâ€ TEXTBOOK - Jaya Saputri, Nova (JR-ELT (Journal of Research in English Language Teaching), 2022)
The importance and need to have communicative skills in English, teaching materials (textbooks) play an important role in teaching English. This study was conducted to determine whether the textbook is in accordance with the communicative activities proposed by Richards and Rodgers in the textbook "Bright An English". The English textbook studied is entitled â€œBright An Englishâ€ (ERLANGGA, 2018). The focus of this research is to analyze communicative activities in English textbooks. This study uses a qualitative descriptive method in conducting research. Textbook analysis has revealed several key findings. Data were collected using documentation analysis. In the textbook, Based on the data obtained, it is clear that there are 68 group work activities, 41 fluency activities and 42 meaningful activities in the textbook. The total percentage is 78%. This shows that the textbooks apply more CLT principles based on Richard's theory.